Continuous renal replacement therapy during extracorporeal membrane oxygenation run: a questionary-based survey - Dalal, Parth; Jayakumar, Indira; Gude, Anupama (International Journal of Research in Medical Sciences, 2023)
Background: Extracorporeal membrane oxygenation is becoming a broadly available form of prolonged cardiopulmonary support. Given a higher risk of complications fluid overload and acute kidney injury with ECMO, its conjugation with renal replacement therapy is seems to be beneficial in correcting acid-base and electrolyte imbalance and fluid overload. ECMO with RRT is rarely used in Indian centers. This survey gathered expert’s opinion for routinely faced clinical questions related to ECMO run during RRT/Continuous RRT. Methods: This was a questionary-based survey wherein a structured questionnaire composed of seven questions about ECMO run during RRT/CRRT was mailed as Google form to randomly selected 23 physicians and their responses have been received within one month duration (November 2022 to December 2022). Results: Fluid overload (65.2%) and AKI (47.8%) were found to be the most common indications to put a patient on RRT while ECMO. Almost responders (36.4%) stated that 20-40% patients required RRT while on ECMO. Continuous venovenous hemodiafiltration (47.8%) was the most preferred choice of RRT while on ECMO. Hypotension (38.1%), electrolyte disturbance (14.3%), and hemolysis (23.8%) were the three most common complications in patient on CRRT with ECMO. Majority of the experts feel that introducing CRRT with ECMO circuit was moderately challenging. Conclusions: Clinicians should consider the early introduction of CRRT to address acute kidney injury and fluid overload in the ECMO population. With this survey, we would like to spread awareness among physicians about important aspect CRRT during ECMO.